The dynamics of the Ancient Tula wells cultural landscape: Environmental and social history, ca, 1560 to the present. - Tiki, W. (Norwegian University of Life Sciences, 2010)
This thesis examines the dynamics of ancient tula wells cultural landscape in the Borana plateau of Ethiopia. The thesis has two sections. The first part introduces concepts and provides background and information for reconstructing the environmental and social history of ancient water systems. The second part presents an analysis of the impacts of natural disasters, socio-political perturbations, human responses, human perceptions of land use changes, and labour and technological transformations in the utilizations of tula wells.